KOMUNIKASI PENDIDIK DAN PESERTA DIDIK DALAM PEMBELAJARAN TEMATIK INTEGRATIF di SD/MI - Fatahillah, Fatahillah (Jurnal Tawadhu, 2019)
Educator communication to students has an important role in the teaching and learning process, therefore the ability to communicate becomes one of the competencies that must be possessed by an educator. The learning process is essentially a process of communication, the delivery of messages from the introduction to the recipient. The message delivered is in the form of content / teachings which are poured into communication symbols, both verbal (words and writing) and non-verbal. effective, empathic and empathetic communication, is very influential on the message to be conveyed to students, In the use of educator communication strategies with students in SD / MI there are several things that need to be considered in the learning process, namely: recognizing the target of communication, the choice of communication media , assessment of the purpose of communication messages, and the role of educators as communicators in communication with students. The use of effective communication methods can be done by: Informative communication methods, persuasive communication methods, and instructive / coercive communication. Every communication that is established must have obstacles faced, educators need to pay attention or avoid things that interfere with the delivery channel of the message in the form of channel interference and semantics.